2021
DOI: 10.1186/s13071-021-04754-x
|View full text |Cite
|
Sign up to set email alerts
|

Semi-field evaluation of the exposure-free mosquito electrocuting trap and BG-Sentinel trap as an alternative to the human landing catch for measuring the efficacy of transfluthrin emanators against Aedes aegypti

Abstract: Background The human landing catch (HLC) measures human exposure to mosquito bites and evaluates the efficacy of vector control tools. However, it may expose volunteers to potentially infected mosquitoes. The mosquito electrocuting trap (MET) and BG-Sentinel traps (BGS) represent alternative, exposure-free methods for sampling host-seeking mosquitoes. This study investigates whether these methods can be effectively used as alternatives to HLC for measuring the efficacy of transfluthrin emanator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…A more environmentally sound approach is to use trapping systems that result in the capture, death or sterilization of vectors 233 . For mosquito vectors, these methods include mass-trapping with sticky gravid traps placed in 60-80% of homes, dry attractive toxic sugar bait, electromechanical traps, and traps coupled with ultralow-volume spraying [234][235][236] . A novel approach is the use of inactivated yeast interfering RNA formulations that are specific for killing mosquito larvae 237 .…”
Section: Vector Controlmentioning
confidence: 99%
“…A more environmentally sound approach is to use trapping systems that result in the capture, death or sterilization of vectors 233 . For mosquito vectors, these methods include mass-trapping with sticky gravid traps placed in 60-80% of homes, dry attractive toxic sugar bait, electromechanical traps, and traps coupled with ultralow-volume spraying [234][235][236] . A novel approach is the use of inactivated yeast interfering RNA formulations that are specific for killing mosquito larvae 237 .…”
Section: Vector Controlmentioning
confidence: 99%
“…Therefore, the BB’s residual efficacy is currently unknown. Similarly to ITCs, transfluthrin-based VPSR efficacy over time is dependent on exposure to UV and other environmental parameters (rainfall, wind), as well as the susceptibility of local mosquitoes to pyrethroids [18,19,56,56,68,77]. For this field study, insecticide susceptibility testing to pyrethroids, including etofenprox and transfluthrin, was not feasible due to issues with keeping field-caught adult Anopheles alive and other logistical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The hourly human landing rate (HLR) for the control arm across the 49 collection nights was estimated as a proxy for the hourly human biting rate (HBR) [55,56].…”
Section: Methodsmentioning
confidence: 99%
“…it can be labour intensive and taxing on volunteers when done at large scale [ 26 , 49 ], and can be challenging to standardize due to differences in human attractiveness to mosquitoes, skilfulness of collectors, and alertness throughout the collection period [ 25 , 26 ]. Evaluations of the Mosquito Electrocuting Trap (MET) and Biogents Sentinel Trap (BGS) for measurement of the PE of SR using Aedes aegypti have also shown some promise in semi-field experiments if observations are independent because it was observed that mosquitoes divert from traps to nearby humans [ 50 ].…”
Section: Discussionmentioning
confidence: 99%